Dry Matter Remobilization and Compensatory Effects in Various Internodes of Spring Wheat under Water Stress. Issue 1 (1st January 2014) - Ma, Jian; Huang, Gao‐Bao; Yang, De‐Long; Chai, Qiang
ABSTRACT: Dry matter reserved in vegetative tissues can be remobilized and contribute to crop yields. This study determined the magnitude of dry matter (DM) remobilization from various internodes in spring wheat ( Triticum aestivum L .) under different water stresses. We hypothesized that the ability of DM remobilization differed between genotypes. The genotypes LC26 and LC27 were grown in a rain shelter facility under nonstress, moderate stress, and severe water stress during grain filling. Compared with the nonstress check, LC27 remobilized 22 mg plant −1 more preanthesis DM in its upper internodes under moderate stress and 32 mg plant −1 more under severe stress. Remobilization efficiency (percent maximum DM remobilized) increased by 110% in the stem, 137% in the lower internodes, and 33% in the upper internodes, under severe stress. Wheat grain yield was reduced by 21% under moderate stress and by 43% under severe stress compared with the nonstress check, but lost yields were partly compensated by DM remobilization. Remobilized DM from the stem of LC26 contributed 18% to the grain yield under nonstress, 27% under moderate stress, and 39% under severe stress. Dry matter reserved in the stem of LC27 contributed 13% to the grain yield under nonstress, 18% under moderate stress, and 37% under severe stress. The compensation from DM remobilization did not offset the lost yield, and thus, improved practices are required to manage soil water and to minimize yield losses caused by drought stress.